EKOWISATA BERBASIS MASYARAKAT WISATA ALAM PANTAI KUBU - Vita Yanuar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Kubu Beach were originally just a coastal plain, has now been changed into nature in the village of Kubu, District Kumai, West Kotawaringin. The active role of the community around the village and related agencies that maintain and preserve the Kubu Beach so that more eligible to be a natural tourist attraction. Community-based ecotourism has been applied in the management of this nature Kubu Beach is to involve local communities in tourist areas both onshore and natural preserve economic activity (trade). The purpose of this study is to open the mindset of society towards nature preservation Kubu Beach and make it a community-based ecotourism. This research is descriptive inference to determine the number of samples using the technique Quota Sample of 100 people (50 visitors and 50 people around the tourist areas). The results showed that the natural scenic beauty still awake and demand by visitors (25 %) and local community (28 %). This indicates that the natural attractions worthy of being the Kubu Beach getaways / recreation by heeling the number of visitors Ý = 31.604,17 + 3.511,18 X with the value of a positive slope. Communities around the region also plays an active role in the development of ecotourism Kubu Beach is not only to preserve the beach but also generate economic activity around the tourist areas (23 %). In addition, visitors also take an active role in maintaining the beauty and cleanliness of the area's nature (25 %).